The Effect of Price and Non-Price Factors on the Alcoholic Beverage Consumption of Millennials in the City of Caloocan - Angel Joyce Sophia Cordero; Audre Garett Balayan; Jefferson Paspie; Ronaldo Cabauatan (UJoST- Universal Journal of Science and Technology, 2022)
The study examines the impact of excise tax (price factor), alcohol sales restrictions, media advertisements, and health warning labels (non-price factors) on the alcoholic consumption of millennials in Caloocan City, Philippines. The study identifies whether such factors imposed and used significantly reduce alcohol use among millennials. Previous empirical research shows that all factors have either increased or decreased alcohol use. Nevertheless, excessive consumption of alcohol leads to various negative externalities which cause harmful impacts on a household or a community. This research identifies if the price and non-price factors are effective approaches or strategies for controlling the consumption of alcoholic beverages. This study uses regression analysis through Ordinary Least Squares to analyze the data gathered through a survey. The findings of the study show that imposition of excise tax and placing health warning labels has a statistically significant effect on reducing alcohol use. Meanwhile, sales restrictions and media advertisement does not have a significant impact. Furthermore, researchers recommend that policymakers impose a higher excise tax rate and place health warning labels on alcohol containers to reduce its consumption and lessen its related harms among individuals and their surroundings.